The Vertigo of Technology and its Uncanniness - Ferreira, Gabriela Semensato (Revista Investigações, 2015)
Published for the first time during the 1930’s Great Depression, Vertigo is a “wordless novel”, according to its author Lynd Ward. This work marks the historic moment when various technologies are integrated to the urban life, such as the train, the telephone and the cars, showing how these changes interact with the capitalist crisis lived at that time. Thus, Ward recreates multiple sensations of vertigo using the woodcutting technique in this precursor of the graphic novel. This article relates the impacts of technology to the notion of uncanny and the reception of this work among artists.